Internet of Things Based Smart Woman Security System using GSM and GPS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This Project presents an automotive localization system using GPS and GSM-SMSservices and alerts over IOT for woman security. The system permits localization of the womanand transmitting the position to the rescue team as a short message (SMS) and over Internet. Thesystem can be interconnected with the car alarm system and alert the surrounding people to helpwoman. This security tracking system is composed of a GPS receiver, Microcontroller, and a GSMModem and IOT module. When woman need help that time, she will press security alert switchthen GPS Receiver gets the location information from satellites in the form of latitude andlongitude with alert through IOT. The Microcontroller processes this information, and thisprocessed information is sent to the certain person using GSM modem. The presented applicationis a low-cost solution for woman in risk. The proposed solution can be used in other types ofapplication like child security, woman security, where the information needed is requested rarelyand at irregular period of time (when requested).